A religiosidade popular na caminhada de fé com Maria de Mojuí dos Campos a Santarém (1955-2017) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
This work is the result of a research carried out in the context of the Walk of Faith with Mary with approaches related to the political and economic social trajectory. This walk is a form of pilgrimage created in 1995 with a route of about 37 kilometers that leaves the Municipality of Mojuí dos Campos to the central cathedral of Santarém. The objective of this work is to analyze the faith journey with Mary as an instrument of pilgrimage, understanding its political and social role, presenting a historical panel that led to the creation of the Walk of Faith with Mary event, reflecting on the aspects of popular Catholic religiosity present in this manifestation cultural. The methodology used was documentary research (journal of the party, minutes, newspapers), complementing information obtained through interviews; and bibliographic research, where there is a study through the different approaches on the theories elaborated by several authors on the subject, investigating the view of the theoreticians, with the purpose of discovering answers to the questions pertinent to the research. As a result of this work, it was possible to reflect on attitudes, behaviors, representations, social, cultural and symbolic of the feast of Our Lady of Conception under a prism that leads us to understand how the ruptures occur, the relations between what is sacred or profane at popular festivals, considered religious over the years.
Keywords: Religiosidade popular; Catolicismo; Caminhada - Maria; Fé; Representações sociais; CNPQ:: CIÊNCIAS HUMANAS